High Prevalence of Anaplasma spp. in Small Ruminants in Morocco. Issue 1 (27th April 2015) - Ait Lbacha, H.; Alali, S.; Zouagui, Z.; El Mamoun, L.; Rhalem, A.; Petit, E.; Haddad, N.; Gandoin, C.; Boulouis, H‐J.; Maillard, R.
Summary: The prevalence of infection by Anaplasma spp. (including Anaplasma phagocytophilum ) was determined using blood smear microscopy and PCR through screening of small ruminant blood samples collected from seven regions of Morocco. Co‐infections of Anaplasma spp., Babesia spp, Theileria spp. and Mycoplasma spp. were investigated and risk factors for Anaplasma spp. infection assessed. A total of 422 small ruminant blood samples were randomly collected from 70 flocks. Individual animal (breed, age, tick burden and previous treatment) and flock data (GPS coordinate of farm, size of flock and livestock production system) were collected. Upon examination of blood smears, 375 blood samples (88.9%) were found to contain Anaplasma‐like erythrocytic inclusion bodies. Upon screening with a large spectrum PCR targeting the Anaplasma 16S rRNA region, 303 (71%) samples were found to be positive. All 303 samples screened with the A. phagocytophilum‐ specific PCR, which targets the msp2 region, were found to be negative. Differences in prevalence were found to be statistically significant with regard to region, altitude, flock size, livestock production system, grazing system, presence of clinical cases and application of tick and tick‐borne diseases prophylactic measures. Kappa analysis revealed a poor concordance between microscopy and PCR ( k = 0.14). Agreement with PCR is improved by considering microscopy and packed cell volume (PCV) in parallel. The prevalence of double infections was found to be 1.7, 2.5 and 24% for Anaplasma‐Babesia, Anaplasma‐Mycoplasma and Anaplasma‐Theileria, respectively. Co‐infection with three or more haemoparasites was found in 1.6% of animals examined. In conclusion, we demonstrate the high burden of anaplasmosis in small ruminants in Morocco and the high prevalence of co‐infections of tick‐borne diseases. There is an urgent need to improve the control of this neglected group of diseases.